Banana leaf as packaging of lulo for different storage temperatures and the effects on postharvest characteristics (2017)
In Colombia, the small and medium farmers are responsible for the production of nearly 45.000 t yr-1 of lulo (Solanum quitoense). However adequate and easy techniques for postharvest handling are not often available to be implemented by this sector of the producers. This research aimed to study banana (Musa paradisiaca) leaf as primary packaging to minimize the loss of quality of lulo stored at different temperatures. Chemical and physiological quality parameters were considered in the analysis of the maturation process. Loss weight, color changes in CIELAB coordinates, total titratable acidity (TTA), Young’s modulus and firmness were measured to represent the fruit quality. Use of banana leaf as primary package show that weight losses and the color changes result of the ripening process were decreased. The color changes of lulo skin were significantly affected by storage temperature. To avoid changes in TTA, mechanical damage is not recommended. When the lulo fruits were packed with banana leaves, the Young’s modulus and firmness values was higher. The results of this research allow the comparison of quality of lulo in the packaging proposal and the results of others researchers who use conventionally packaging like wood crates and carton packaging. The proposal packaging configuration (lulos packed with banana leaf in plastic crates of 80×60×20 cm) is an easy alternative to get and preserve the quality of lulo fruits for a longer storage time.